Auditors’ Independence, Audit Tenureship, Firm Characteristics and Audit Quality: Evidence from Nigeria - Oziegbe, David; Odien, Ruth (The Journal of Accounting and Management, 2022)
This study aims to empirically examine the effect of auditors’ independence, audit tenureship, firm characteristics on audit quality in Nigeria. The population of the study comprises a sample of ten (10) listed pharmaceutical companies listed on the Nigerian Exchange Group (NGX). The time period for the study covers audited financial statements of the companies from 2013-2019. The study focused on two explanatory variables: auditors’ independence and audit tenure, and two control variables: firm size and firm age. While the dependent variable audit quality was proxied by big four firms and non-big four firms. The secondary source of data was adopted in this study. The data collected were analyzed using the panel regression techniques. The results suggest that all of the explanatory and control variables have a positive and significant effect on audit quality. The study recommends that auditors’ independence is directly proportional to audit quality, thus audit firms should be independent in order to enhance audit quality. Auditor-client engagement should not exceed 3years in order to avoid familiarity threat. In addition, firms are advised to engage the services of one of the big audit firms since it results to improved audit quality. Younger firms should understudy older firms to learn from the experiences that they have acquired over the years that impact positively on audit quality.